Endoscope-Assisted Surgery vs. Burr-Hole Craniostomy for the Treatment of Chronic Subdural Hematoma: A Systemic Review and Meta-Analysis - Guo, Songyi; Gao, Wei; Cheng, Wen; Liang, Chuansheng; Wu, Anhua (Frontiers in Neurology, 2020)
Objectives This article aims to evaluate the safety and effectiveness of endoscope-assisted surgery for chronic subdural hematoma（cSDH） in comparison with the burr-hole craniostomy. Methods Electronic literature research was performed in Medline, the Cochrane library, and Embase from the inception to February 18th, 2020. A systematic review with meta-analyses was conducted to compare the efficacy of endoscope-assisted surgery with BHC surgery. Results This meta-analysis included 4 studies comprising 441 patients. Endoscope-assisted surgery significantly decreased the risk of recurrence in patients with cSDH (OR of 0.38, 95% CI, 0.19-0.76, P=.0.006, I 2=0%). The complication rate was also significantly lower in the endoscope-assisted group. (RR of 0.25, 95%CI, 0.07-0.89, P=0.03, I 2=72% ) Conclusion We conduct the first meta-analysis of endoscope-assisted surgery for cSDH. The meta-analysis of 4 studies comprising 441 patients with cSDH suggests a significantly decreased risk of recurrence and postoperative complications after endoscope-assisted surgery. Therefore, endoscope-assisted surgery is effective and safe in treating cSDH.